БЎЛАЖАК ПЕДАГОГ КАДРЛАРНИ ЎҚИТИШДА МАХСУС МОБИЛ ИЛОВАЛАР ЯРАТИШ ЗАРУРИЯТИ (жисмоний тарбия мисолида) - Тажибаев, С.С. (SCIENCE and SOCIETY, 2020)
The article examines the role of innovative technologies in education and the need to create special mobile applications, including the use of modern mobile applications to enhance the professional knowledge of future physical education teachers.
Keywords: education. physical culture teacher; innovative technology; mobile applications